2015
DOI: 10.1177/0165025415570645
|View full text |Cite
|
Sign up to set email alerts
|

Sharing the past and future among adolescents and their parents

Abstract: This study explored how sharing past and future life events among late adolescents and their parents influenced the quality of their own time perspectives. Triads (N ¼104) of female students and their parents described three important life events from their past and future. The results showed that adolescents who shared past and future life events predicted a positive impact on their time perspective, whereas parents displayed a more complex dynamism that included the impact of sharing the past on the future a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Hudson (2006) has suggested that the kind of parental linguistic stimulation and the involvement in patterns of future-oriented interaction favor future understanding of the child. Moreover, parents differ in how they share future and past experiences to their offspring, and that is related to adolescents' time perspective (Shirai & Higata, 2016). In this line, it is possible to reason that parents' CFC level may be determining the temporal horizon of their actions and the type of interaction and temporal language addressed to their children, which in turn, behaviorally models the acquisition and development of EF in their children.…”
Section: Introductionmentioning
confidence: 99%
“…Hudson (2006) has suggested that the kind of parental linguistic stimulation and the involvement in patterns of future-oriented interaction favor future understanding of the child. Moreover, parents differ in how they share future and past experiences to their offspring, and that is related to adolescents' time perspective (Shirai & Higata, 2016). In this line, it is possible to reason that parents' CFC level may be determining the temporal horizon of their actions and the type of interaction and temporal language addressed to their children, which in turn, behaviorally models the acquisition and development of EF in their children.…”
Section: Introductionmentioning
confidence: 99%